Chapter A new proposal for a strategic and resilient regeneration plan for seaside waterfronts. An Adriatic case: Riccione. - Cesarini, Chiara (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The physical definition of the coastal system and the management definition of same are topics that sets the goal of defining a possible methodological approach through the presentation of the case study for territorial planning.